Efeitos da redução da ninhada e do dimorfismo sexual sobre parâmetros metabólicos e expressão do receptor CB1 no sistema nervoso central de ratos Wistar jovens - Mangerona, Bianca Aparecida (2019)
Obesity is a serious clinical condition that has become one of the major public health problems at the present time. Its origin is multifactorial, involving genetic, metabolic and behavioral factors that result in an imbalance between intake and caloric expenditure, with consequent positive energy balance and weight gain. Several neuronal and endocrine mechanisms are related to the control of energetic homeostasis, including the endocannabinoid system (ECS), a neuroregulation system whose imbalance has been considered an important factor for the development and maintenance of obesity. Using the experimental model of reduced litter [3 pups/litter (SL) vs 10 pups/litter (NL)] we confirmed in 21- and 60-day-old rats the induction of early obesity by postnatal overfeeding by body mass analysis, specific rate of weight gain and the perigonadal (pWAT) and retroperitoneal (rWAT) stores of white adipose tissue. We also investigated the effects of sexual dimorphism on food and water intake and body mass gain, relative mass of tissues related to endocrine and metabolic function (adrenal, pituitary, brown adipose tissue - BAT and WAT), lipid and glycemic profiles and type 1 cannabinoid receptor (CB1) protein or messenger mRNA expression in the hypothalamus or WAT. In the 21-days group, there was a significant increase in body mass in offspring originated from SL mothers, as well as in BAT and pWAT and rWAT masses, lower expression of CB1 after glucose overload and decreased CB1 mRNA levels in rWAT. In the 60-day group, increases in body mass, dietary intake, pWAT and rWAT were found in both genders, as well as in female CB1 mRNA expression in rWAT. No significant differences were found in the relative pituitary and adrenal masses related to litter size. Regarding lipid profile, both female and male SL puppies showed only an increase in total cholesterol plasma levels, while the 60-day group showed an increase in triglyceride plasma concentrations and an increase in CB1 expression in response to glucose ingestion. Sexual dimorphism, in turn, resulted in differences in body mass, dietary intake and pWAT, rWAT, pituitary and adrenal masses, as well in triglyceride and glucose levels and CB1 expression in the hypothalamus in both NL and SL groups. Taken together, these results indicate that postnatal overfeeding was effective in inducing obesity in young animals of both genders, influencing metabolic parameters. Therefore, these results demonstrate the importance of nutrition as a factor of neonatal programming, determining the development of obesity in offspring durign adulthood.